SPECIAL CASES OF DETERMINING THE POSITION OF THE VEHICLE PRIOR TO MANEUVER - S. Zharkikh (Теория и практика судебной экспертизы, 2015)
The paper presents an algorithm for determining the position of the vehicle prior to maneuver using the two-axle vehicle standard steering mode and taking into account the structurally determined minimum turning radius.